Investigation into the sequence structure of 23 Y chromosomal STR loci using massively parallel sequencing. (November 2016) - Kwon, So Yeun; Lee, Hwan Young; Kim, Eun Hye; Lee, Eun Young; Shin, Kyoung-Jin
Highlights: 250 Korean males were sequenced using MPS on PowerPlex ® Y23 loci and a Y-SNP (M175) with small-sized amplicons. Discordant genotypes were observed in DYS385, DYS439, and DYS576 between CE and MPS results. 12 Y-STR loci showed sequence variation and the most varied alleles occurred in DYS389II through the MPS analysis. SNP, deletion, and insertion were observed in the flanking region of DYS481, DYS576, and DYS385, respectively. Stutter and noise ratios of 23 Y-STRs using the developed MPS system were investigated. Abstract: Next-generation sequencing (NGS) can produce massively parallel sequencing (MPS) data for many targeted regions with a high depth of coverage, suggesting its successful application to the amplicons of forensic genetic markers. In the present study, we evaluated the practical utility of MPS in Y-chromosome short tandem repeat (Y-STR) analysis using a multiplex polymerase chain reaction (PCR) system. The multiplex PCR system simultaneously amplified 24 Y-chromosomal markers, including the PowerPlex ® Y23 loci (DYS19, DYS385ab, DYS389I, DYS389II, DYS390, DYS391, DYS392, DYS393, DYS437, DYS438, DYS439, DYS448, DYS456, DYS458, DYS481, DYS533, DYS549, DYS570, DYS576, DYS635, DYS643, and YGATAH4) and the M175 marker with the small-sized amplicons ranging from 85 to 253 bp. The barcoded libraries for the amplicons of the 24 Y-chromosomal markers were produced using a simplified PCR-based library preparation method and successfully sequenced using MPS on a MiSeq ® System with samples from 250 unrelated Korean males. The genotyping concordance between MPS and the capillary electrophoresis (CE) method, as well as the sequence structure of the 23 Y-STRs, were investigated. Three samples exhibited discordance between the MPS and CE results at DYS385, DYS439, and DYS576. There were 12 Y-STR loci that showed sequence variations in the alleles by a fragment size determination, and the most varied alleles occurred in DYS389II with a different sequence structure in the repeat region. The largest increase in gene diversity between the CE and MPS results was in DYS437 at +34.41%. Single nucleotide polymorphisms (SNPs), insertions, and deletions (indels) were observed in the flanking regions of DYS481, DYS576, and DYS385, respectively. Stutter and noise ratios of the 23 Y-STRs using the developed MPS system were also investigated. Based on these results, the MPS analysis system used in this study could facilitate the investigation into the sequences of the 23 Y-STRs in forensic genetics laboratories.